2019
DOI: 10.1002/anie.201908122
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Support Effect in Atomically Dispersed Pt on WO3−x for Utilization of Pt in the Hydrogen Evolution Reaction

Abstract: Single-atom catalysts (SACs) have attracted growing attention because they maximizet he number of active sites, with unpredictable catalytic activity.Despite numerous studies on SACs,t here is little researcho nt he support, which is essential to understanding SAC. Herein, we systematically investigated the influence of the support on the performance of the SACb yc omparing with single-atom Pt supported on carbon (Pt SA/C) and Pt nanoparticles supported on WO 3Àx (Pt NP/WO 3Àx ). The results revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
215
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(233 citation statements)
references
References 34 publications
1
215
1
1
Order By: Relevance
“…The intermixing of palladium and silver occurs during the reduction of oxidized Ag(111) by molecular hydrogen due to the presence of PdO x islands. Previously, migration of hydrogen atoms has been demonstrated away from single metal atoms and metal islands to either a metal or metal oxide host; [19][20][21][22][23][38][39][40][41]63 however, intermixing and reconstruction during reaction was not evident. For example, single palladium atoms in copper promote molecular hydrogen dissociation on palladium and subsequent migration to the copper 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermixing of palladium and silver occurs during the reduction of oxidized Ag(111) by molecular hydrogen due to the presence of PdO x islands. Previously, migration of hydrogen atoms has been demonstrated away from single metal atoms and metal islands to either a metal or metal oxide host; [19][20][21][22][23][38][39][40][41]63 however, intermixing and reconstruction during reaction was not evident. For example, single palladium atoms in copper promote molecular hydrogen dissociation on palladium and subsequent migration to the copper 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that the interface between metal nanoparticles and the metal oxide support can affect chemical behavior by the creation of specific active sites [12][13][14][15][16][17][18] and direct migration or "spillover" 19 of reactive species created on one phase to a neighboring phase of differing reactivity [19][20][21][22][23][24][25] . The metal/oxide support interface can significantly restructure in reactive gas environments on a short timescale of minutes and long length scales of microns 26 .…”
mentioning
confidence: 99%
“…Hydrogen atom spillover (not to be confused with H 2 spillover, which includes dissociation and is an important step for hydrogenation reactions and hydrogen storage) was recognized as the phenomenon responsible for the promotion of Pt electrocatalytic activity towards the hydrogen evolution 47 years ago, for Pt supported on pyrolytic graphite [157]. Several experimental works contributed to the affirmation of H ads spillover as the important step in HER mechanism at Pt/C [158], Pt/transition-metal-oxide [159], Pt/Au [160], Pi/Ni [161], atomically-dispersed-Pt/WO 3-x [162], Pd/Au [163], WO 3 •2H 2 O/WS 2 [164], Rh/MoS 2 [165], Rh/Si (although authors do not employ the term spillover) [166], Pd@Cu(II) phthalocyanine/MOF [82], and Ni/rGO interfaces [70,167,168]. Kinetic Monte-Carlo simulations were employed to investigate the impact of the spillover rate on the rate of H 2 production at the Ni/rGO interface, using the model that was able to qualitatively reproduce the experimentally observed trends [168].…”
Section: Role Of the Metal-support Interfaces In Her Mechanismmentioning
confidence: 99%
“…Hydrogen atom spillover (not to be confused with H2 spillover, which includes dissociation and is an important step for hydrogenation reactions and hydrogen storage) was recognized as phenomenon responsible for the promotion of Pt electrocatalytic activity towards the hydrogen evolution 47 years ago, for Pt supported on pyrolytic graphite [144]. Several experimental works contributed to the affirmation of Hads spillover as the important step in HER mechanism at Pt/C [145], Pt/transition-metal-oxide [146], Pt/Au [147], Pi/Ni [148], atomically-dispersed-Pt/WO3-x [149], Pd/Au [150], WO3·2H2O/WS2 [151], Rh/MoS2 [152], Rh/Si (although authors do not employ the term spillover) [153], Pd@Cu(II) phthalocyanine/MOF [69], and Ni/rGO interfaces [154,155]. Kinetic Monte-Carlo simulations were employed to investigate the impact of spillover rate on the rate of H2 production at Ni/rGO interface, using the model that was able to qualitatively reproduce the experimentally observed trends [155].…”
Section: Role Of the Metal-support Interfaces In Her Mechanismmentioning
confidence: 99%